PENGARUH TENAGA KERJA TERHADAP PRODUKTIVITAS PROYEK PEMBANGUNAN GEDUNG POLIKLINIK FAKULTAS KEDOKTERAN UNIVERSITAS PATTIMURA AMBON - Assel, Mei Salsabila; Selly Metekohy; Langi, Jeffrey Payung (Jurusan Teknik Sipil, 2023)
A construction project is a series of activities related to the process of building an infrastructure with a predetermined time limit to estimate the time required to complete the project. In project planning, of course, work productivity must be considered. Especially on factors that can affect work productivity such as age factor, education factor and experience factor. The Polyclinic Building Project, Faculty of Medicine, Pattimura University, Ambon, is one of the government projects that costs up to Rp. 1,711,968,000.00-. The method used in this research is validation test, reliability test, F test and T test using the SPSS V16 tool where in this method the data from the questionnaire will be obtained which will then be analyzed with the SPSS V16 tool. The results obtained. Based on the results of data analysis that has been carried out, it is obtained that 1) the experience factor (X1) has a partial effect on labor productivity in the Polyclinic Building Project, Faculty of Medicine, Pattimura University, Ambon, first floor work, Phase I with a sig value of 0.000 < 0, 05. 2) The age factor (X2) has a partial effect on labor productivity in the Polyclinic Building Project, Faculty of Medicine, Pattimura University, Ambon, on the first floor, with a sig value of 0.000 <0.05. and 3) Educational factor (X3) has a partial effect on labor productivity in the Polyclinic Building Project, Faculty of Medicine, Pattimura University, Ambon, on the first floor, with a sig value of 0.000 <0.05.